Management of Material Component Development in Multicultural Islamic Education Curriculum - Ramdanil Mubarok (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
This article will analyze and interpret the concepts of the components of the multicultural PAI curriculum, the learning process and management of the development of the components of the multicultural Islamic religious education teaching materials at SMK Nusa Unggul Husada. This research is qualitative. The development model used is the McKenny model which consists of preliminary analysis, planning stages, and evaluation. The research subjects were students of SMK Nusa Unggul Husada. The research instruments are observation sheets, interviews, assessment sheets, evaluation sheets and validation sheets. Furthermore, data processing is carried out with qualitative description. Data were analyzed comprehensively according to the characteristics of qualitative research. The result is that the concept of material components in the multicultural PAI curriculum is a series of activities carried out in the form of compiling and developing content to achieve goals. Multicultural PAI learning at Nusa Unggul Husada Vocational School is focused on understanding multicultural Islamic religious education materials comprehensively and then being applied in a multicultural school environment in terms of language, culture, religion, ethnicity, and even gender diversity. The development of the components of teaching materials in the learning process that has been carried out illustrates the validity of the learning tools. The use of multicultural PAI learning tools as a whole falls into the practical category in terms of the implementation of the implementation plan.